2014
DOI: 10.1089/neu.2013.3245
|View full text |Cite
|
Sign up to set email alerts
|

GFAP Out-Performs S100β in Detecting Traumatic Intracranial Lesions on Computed Tomography in Trauma Patients with Mild Traumatic Brain Injury and Those with Extracranial Lesions

Abstract: Both glial fibrillary acidic protein (GFAP) and S100β are found in glial cells and are released into serum following a traumatic brain injury (TBI), however, the clinical utility of S100β as a biomarker has been questioned because of its release from bone. This study examined the ability of GFAP and S100β to detect intracranial lesions on computed tomography (CT) in trauma patients and also assessed biomarker performance in patients with fractures and extracranial injuries on head CT. This prospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(191 citation statements)
references
References 31 publications
8
176
3
4
Order By: Relevance
“…19 A recently published study in 397 adult trauma patients compared the performance of S100b with GFAP in predicting intracranial lesions on CT in the presence of torso and limb fractures. 18 Overall, GFAP out-performed S100b in detecting CT lesions and did considerably better in detecting such lesion in multiple trauma when extracranial fractures were present. GFAP is detectable in serum in less than 1 h after a mild TBI and can distinguish mild TBI patients from other trauma patients.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…19 A recently published study in 397 adult trauma patients compared the performance of S100b with GFAP in predicting intracranial lesions on CT in the presence of torso and limb fractures. 18 Overall, GFAP out-performed S100b in detecting CT lesions and did considerably better in detecting such lesion in multiple trauma when extracranial fractures were present. GFAP is detectable in serum in less than 1 h after a mild TBI and can distinguish mild TBI patients from other trauma patients.…”
Section: Introductionmentioning
confidence: 88%
“…13,14 Glial fibrillary acidic protein (GFAP) has been shown to be a promising brain-specific biomarker for mild TBI. [15][16][17][18] GFAP is a monomeric intermediate protein that was first isolated by Eng and colleagues in 1971 and found in astroglial skeleton in both white and gray brain matter. 19 A recently published study in 397 adult trauma patients compared the performance of S100b with GFAP in predicting intracranial lesions on CT in the presence of torso and limb fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, any increase in the level of serum GFAP can depend on the magnitude of brain damage and its duration. It was observed that serum GFAP level was increased in different neurological diseases with characteristic persistent and chronic brain damage, including multiple sclerosis, glioblastoma, Parkinson disease, traumatic brain injury, and subarachnoid haemorrhage [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The GFAP blood concentrations in patients with mTBI in the emergency department is better than the s100B blood concentrations in predicting the need for brain CT. Especially, in cases of extracranial injuries, GFAP blood concentrations were also found to have a higher specificity for detecting lesions that could be confirmed with brain CT [77]. In addition, in 2 reviews, the concentrations of GFAP correlated with the initial GCS scores, as with s100B [59,60].…”
Section: Gfapmentioning
confidence: 91%